Cultivating Secondary Traumatic Growth Among Healthcare Workers: The Role of Social Support and Self‐Efficacy. Issue 9 (13th January 2014) - Shoji, Kotaro; Bock, Judith; Cieslak, Roman; Zukowska, Katarzyna; Luszczynska, Aleksandra; Benight, Charles C.
<x xml:space="preserve">Abstract</x> Objective This 2‐study longitudinal investigation examined the indirect effects of secondary traumatic stress (STS) on secondary traumatic growth via two mediators: perceived social support and secondary trauma self‐efficacy. In particular, we tested if the 2 hypothetical mediators operate sequentially, that is, with secondary trauma self‐efficacy facilitating social support (i.e., cultivation hypothesis) and/or social support enhancing self‐efficacy (i.e., enabling hypothesis). Method Participants in Study 1 (N = 293 at Time 1, N = 115 at Time 2) were behavioral healthcare providers working with U.S. military personnel suffering from trauma. Study 2 was conducted among Polish healthcare workers (N = 298 at Time 1, N = 189 at Time 2) providing services for civilian survivors of traumatic events. Results In both studies, multiple mediational analyses showed evidence for the cultivation hypothesis. The relationship between STS at Time 1 and secondary traumatic growth at Time 2 was mediated sequentially by secondary trauma self‐efficacy at Time 1 and social support at Time 2. The enabling hypothesis was not supported. Conclusion Education and development programs for healthcare workers may benefit from boosting self‐efficacy with the intent to facilitate perceived social support.